Physico-chemical, microbiological, and sensory characteristics of yogurt as affected by various ingredients - Aleman, Ricardo S.; Cedillos, Roberto; Page, Ryan; Olson, Douglas; Aryana, Kayanush (Journal of dairy science, 2023)
l-Glutamine, quercetin, slippery elm bark, marshmallow root, N-acetyl-d-glucosamine, licorice root, maitake mushrooms, and zinc orotate have been reported to help treat leaky gut. The purpose of this research was to explore the impact of these functional ingredients on the physico-chemical, microbiological, and sensory properties of yogurt. The milk from same source was equally divided into 9 pails and the 8 ingredients were randomly assigned to the 8 pails. The control had no ingredient. Milk was fermented to yogurt. The pH, titratable acidity, syneresis, viscosity, color (L*, a*, b*, C*, and h*), Streptococcus thermophilus counts, and Lactobacillus delbrueckii spp. bulgaricus counts of yogurts were determined on d 1, 7, 14, 21, 28, 35, and 42, whereas coliform counts, yeast and mold counts, and rheological characteristics were determined on d 1 and 42. The sensory study was performed on d 3 and particle size of the functional ingredients (powder form) was also determined. When compared with control, the incorporation of slippery elm bark into yogurts led to less syneresis. l-Glutamine increased pH and n′ values (relaxation exponent derived from G′) and lowered titratable acidity values. N-Acetyl-d-glucosamine incorporation resulted in higher n′ and lower titratable acidity values, whereas maitake mushroom led to lower n′ values. Incorporating quercetin increased the growth of L. bulgaricus. Adding maitake mushrooms increased the growth of S. thermophilus but lowered apparent viscosity values, whereas quercetin decreased its S. thermophilus counts. Quercetin decreased L* and a* values but increased b* values, and maitake mushroom increased a* values. Thixotropic behavior increased with the addition of licorice root and quercetin. Adding slippery elm bark, N-acetyl-d-glucosamine, licorice root, maitake mushrooms, and zinc orotate into yogurt did not affect the sensory properties, whereas yogurts with quercetin had the lowest sensory scores. Overall, most of these ingredients did not cause major changes to yogurt properties.